Leningrad : Siege and Symphony - Moynahan, Brian, 1941- (London Quercus, 2014)
Leningrad: Siege and Symphony sets the composition of Shostakovich's most famous work against the tragic canvas of the siege itself and the years of repression and terror that preceded it.
Include Index
Keywords: Russia (Federation)--Saint Petersburg -- Siege of Saint Petersburg (Russia : 1941-1944) -- Symphonies (Shostakovich, Dmitriĭ Dmitrievich)